PENGARUH PENERAPAN METODE PEMBELAJARAN MANDIRI DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AKIDAH AKHLAK KELAS XI DI MA MA’HAD DIRASATIL ISLAMIYAH WAL ‘ARABIYAH TAQWA MAKASSAR - Nur Fahmi; H.Bisry Abdul Karim,LC.,MA; Surani; Ahmad Syahid; Bambang Sampurno; Abdul Wahab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the implementation of the independent learning method in improving students’ learning motivation in the subject of Aqidah Akhlak for Grade XI at MA Ma’had Dirasatil Islamiah Wal’arabiah Makassar. The purpose of this study is to analyze the learning process by applying the independent learning method in Aqidah Akhlak classes and to determine whether the independent learning method can improve the learning motivation of Grade XI students at MA Ma’had Dirasatil Islamiah Wal’arabiah Taqwa Makassar. The type of research used is Classroom Action Research conducted in two cycles. The procedure in this Classroom Action Research consists of four main components: planning, action, observation, and reflection. The relationship among these four components is considered as one cycle. The research subjects were 27 Grade XI students, consisting of 14 male students and 13 female students. The data collection techniques used in this study were observation, interviews, tests, and documentation. The results of the study show that before conducting Cycle I, a pre-test was administered to determine the students’ initial abilities. In the pre-cycle stage, 10 students achieved mastery with a percentage of 30.04%, meeting the minimum score of 70. Meanwhile, 17 students (60.74%) did not achieve mastery, and the average score was only 61.21, categorized as low. In Cycle I, 12 students achieved mastery with a percentage of 44.44%, while 15 students (55.56%) did not achieve mastery. The average score increased to 71.51, categorized as moderate. In Cycle II, all 27 students achieved mastery with a percentage of 100%. Based on the research findings, it can be concluded that the implementation of the independent learning method can improve the learning outcomes of Grade XI students at MA Ma’had Dirasatil Islamiah Wal’arabiah Makassar.